PREPARATION OF A COMPOSITION BASED ON PE FILLED WITH MINERAL COMPOUNDS AND MODIFIED WITH PVC - Irade Abdullayeva Gurban; Ramin Penahov Ramiz (World Scientific Reports, 2026)
modern industry requires constant improvement of the technical and consumer properties of polymeric materials for the production of a wide range of products. Obtaining and researching the properties of polymer mixtures based on already known large-tonnage polymers in order to obtain new polymer materials and expand the range of products is promising, since obtaining materials with new properties by synthesis is a long and labor-intensive process.Since polyethylene and polyvinyl chloride are the most commonly used materials in the production of disposable packaging and containers compared to other large-tonnage polymers, the issue of recycling these two materials is very relevant. In this context, a lot of research is being carried out and is being carried out on the possibility of combining PVC and PE in an alloy and obtaining compositional products from them.The obtained indicators are analyzed using a number of research methods on the prepared sample. These indicators were analyzed by the method of swelling rate, zol-gel fraction analysis, infrared spectroscopy